2018
DOI: 10.4038/sljfa.v4i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Determination of shelf-life of <i>Trichoderma asperellum </i> in solid- and liquid-based formulations

Abstract: Trichoderma has gained attention as a promising bio-control agent owing to its effectiveness against a wide array of soil-borne plant pathogens. Successful introduction of bio-control agents to farmers is hindered mostly by unavailability of commercial preparation of Trichoderma bio-inoculate with a considerably higher shelf-life. The objectives of this investigation was to study the shelf-life of T. asperellum in selected liquid-and solid-based formulations and to find the suitability of cattle manure as a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Different substrates are now utilized as carriers to enhance quality, extend shelf life, and boost the activity of potent microbes [104]. Looking at the development of formulations for Trichoderma asperellum, Kodithuwakku and Wijekoon [105] developed both liquid and solid media. Each liquid medium contained 1% sucrose solution, 1% peptone water, 1% tryptone broth, and 1% tryptone soy broth and sterilized distilled water.…”
Section: Application Of Endophytic Fungi In Real Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different substrates are now utilized as carriers to enhance quality, extend shelf life, and boost the activity of potent microbes [104]. Looking at the development of formulations for Trichoderma asperellum, Kodithuwakku and Wijekoon [105] developed both liquid and solid media. Each liquid medium contained 1% sucrose solution, 1% peptone water, 1% tryptone broth, and 1% tryptone soy broth and sterilized distilled water.…”
Section: Application Of Endophytic Fungi In Real Fieldsmentioning
confidence: 99%
“…Interestingly, talc powder showed preservation of spores for three months in a talc-based formulation stored under 25-30 • C in polypropylene bags without adding preservatives. Moreover, Kodithuwakku and Wijekoon [105] revealed that talc with sterilized cattle manure had proved to be an effective multiplication substrate for T. asperellum for commercial production. In a study, Thangavelu et al [106] recognized that soil application of T. harzianum in dried banana leaves (treated with jaggery solution) shows the stimulation of the endophyte growth over the talc-based formulation.…”
Section: Application Of Endophytic Fungi In Real Fieldsmentioning
confidence: 99%